Evaluation of open university education quality in Egypt from the point of view of service providers and stakeholders - Mahmoud Fathi Okashah; Suhair Muhammad Hawalah (University of Science and Technology, Yemen, 2010)
Abstract                                                                                            The study aimed at evaluating open university education quality in Egypt from the point of view of service providers and stakeholders through identifying the factors that contributed to students enrollment and the components of the system that contributes the most to improving this kind of educational system. The study used the descriptive approach and developed a questionnaire to reflect on the responses to predict the factors that contribute the most to developing the system. The sample included students of level four, the teaching staff and administrative technicians. The study found the following: Program components came first based on the responses, then the administrative system, next media and finally fund.     Key words:Evaluation of university education quality - open education -components of open education